Fatigue assessment of cement-treated base for roads: An examination of beam-fatigue tests - Peerapong Jitsangiam (2018)
© 2016 American Society of Civil Engineers. This paper presents an examination of the fatigue characteristics of cement-treated base (CTB), a cement-stabilized material for use in road pavement construction based on CTB beam test specimens prepared and tested under laboratory conditions. The beam fatigue protocol for asphalt concrete, following the Austroads standard test method of AG:PT/T233, were adapted to examine the fatigue characteristics of the CTB test specimens. Standard road base (Granite/Diorite) from the local quarry in Western Australia was employed as the parent material of CTB. The beam-fatigue tests were conducted under the strain-controlled (constant strain) and stress-controlled (constant stress) testing conditions with varying cement contents (3-10%) of CTB test specimens. Two different loading waveforms of sinusoidal and haversine load curves were also investigated. The results show that for the strain-controlled testing condition, the fatigue characteristics of the CTB test specimens were not affected by the difference in both loading waveforms. Furthermore, the fatigue characteristics of the CTB test specimens were significantly influenced by the levels of the applied strains. Under the strain-controlled testing condition, the test results also indicated the existence of fatigue endurance limit, which occurred based on the test condition of the applied strain level of 150 microstrains or less subjected to 5% cement specimens. This fatigue endurance limit increased with respect to higher cement content and initial cyclic flexural stiffness. For the stress-controlled testing condition, this study found that the conclusion cannot be made that a relationship exists between applied stress level and fatigue characteristic of the CTB test specimens. This is because half of the test specimens in this study were damaged in the early stages of loading cycles with small increases in applied stress levels. Considering all the test results, the strain-controlled testing was preferable, based on the test conditions and environment used in this study. This study confirms that the use of the adapted beam-fatigue test protocol of asphalt concrete is suitable to determine the CTB fatigue characteristics, which are difficult to obtain with no standard test protocol. This would lead to more effective use of this material in road pavement design and construction.